Clinical characteristics and in hospital outcomes of heart transplant recipients undergoing percutaneous coronary intervention: Insights from the National Inpatient Sample. Issue 6 (13th August 2020) - Shah, Harshil; Patel, Shakumar; Solanki, Shantanu; Wudexi, Ivan; Singh, Jagmeet; Mullangi, Sanjana; Shah, Priyal; Sarker, Khadiza; Shah, Chail; Patel, Achint
Abstract: Objectives: Cardiac transplant patients are at increased risk of Coronary Allograft Vasculopathy which requires percutaneous coronary intervention (PCI). Background: We aim to determine national epidemiology describing trends, mortality, and morbidity risks in patients with heart transplant undergoing PCI. Methods: We used Nationwide Inpatient Sample (NIS) data from 2002 to 2014 to identify adult hospitalizations with PCI using ICD 9 codes. Acute myocardial infarction (AMI), cardiac transplant status and complications were identified using validated ICD‐9‐CM diagnosis codes. Endpoints were in‐hospital mortality and peri‐procedural complications. Propensity match analysis was performed to compare the end‐points between DES and BMS. Results: Total 8, 613, 900 patients underwent PCI, of which 1, 531(0.002%) patients had prior heart transplant status. Among these 1, 531 PCIs, 311(20%) were due to AMI including 125(8%) due to STEMI. 74% of PCIs were done in males and 78% of the PCIs were performed in the 60–79 age group. Out of 1, 380 stents placed, 1, 090 were DES (79%) and 290 (21%) were BMS. Mortality was higher in the BMS versus DES (8.34% vs. 3.45%, p = .012), Conclusion: We concluded that majority of the population who underwent PCI were older males. DES was used more than BMS. The use of BMS is associated with increased mortality, cardiac complications and Acute Kidney Injury requiring dialysis compared with DES which likely is representative of preferential use of DES in these patient population.